INVESTIGATION OF SUPER ABSORBENT POLYMERS AND ZINC SULFATE ON THE YIELD AND YIELD COMPONENTS OF Calendula officinalis L. - Fatemeh Nejatzadeh-Barandozi (Acta Scientiarum Polonorum: Hortorum Cultus, 2019)
Calendula officinalis L. is one of the most valuable medicinal plants of Asteraceae family and is widely used in the pharmaceutical, health, and food industries. To evaluate the effect of different treatments of super absorbent and zinc sulfate fertilizer on the yield and yield components of Calendula officinalis L., this experiment was conducted at the Islamic Azad University of Khoy. This was a factorial experiment using as the first factor super absorbent polymers at four levels to the soil (0, 4, 6, 8 g/kg) and as the second factor, 4 zinc sulfate concentrations of 0, 25, 50, and 70 mg per pot (based on a randomized complete block design with three replications). The results showed that super absorbent polymers had significant effect on all yield traits, but Zn sulfate fertilizer had only a significant effect on flower diameter, number of stems, total biomass with seeds, total biomass yield, seed yield, and harvest index. The interaction of the super absorbent polymers and zinc sulfate fertilizer increased the plant height, total biomass with seeds and flowers, seed weight, and flower and seed harvest index, whereas the diameter of flowers, number of stems, dry flower yield, flower number per m2, and seed yield were not affected. Super absorbent polymers with zinc sulfate fertilizer had the greatest effect on most yield traits and had a positive effect on increasing the yield components of Calendula officinalis L., which improved the grain yield. The use of super absorbent polymers can improve the water holding capacity of the soil, which reduces the need for water and improves the yield in arid and semi-arid areas.